Mass Media’s Editorship: Basic Principles of the Organization and Management - Maksim Nikolaevich Kim (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article touches upon variety aspects of editorial activity. A special attention is given to the base foundations of labour organization and journalist management team because only such work of media professionals can be acquire the harmonious and targeted character. In the situation when new media spark off restructing of journalistique organizations and institutions, there still remains the question about what the basic principles have remained the same, and which of them require adjustments.